2016
DOI: 10.4103/0019-5154.177755
|View full text |Cite
|
Sign up to set email alerts
|

Approach to infantile hemangiomas

Abstract: Infantile hemangiomas are a group of vascular tumors and are considered to be one of the most common tumors in infancy. Ambiguity still prevails over its origin, etiopathogenesis, and optimal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…5,21 Several theories have been proposed, of which Folkman Klagsbrun placental theory, endothelial progenitor cell theory, hypoxia theory, and angiogenesis theory are the most accepted. 3 GLUT-1, Lewis Yantigen, FcyRII, merosin, and VEGF were involved in the pathophysiology of infantile hemangioma. 22 In the present study, with peptidomics analysis on infantile hemangioma tissue, a total of 192 differentially expressed peptides derived from 34 precursor proteins were identified compared with matched normal skin.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…5,21 Several theories have been proposed, of which Folkman Klagsbrun placental theory, endothelial progenitor cell theory, hypoxia theory, and angiogenesis theory are the most accepted. 3 GLUT-1, Lewis Yantigen, FcyRII, merosin, and VEGF were involved in the pathophysiology of infantile hemangioma. 22 In the present study, with peptidomics analysis on infantile hemangioma tissue, a total of 192 differentially expressed peptides derived from 34 precursor proteins were identified compared with matched normal skin.…”
Section: Discussionmentioning
confidence: 98%
“…Molecular mechanisms of hemangioma formation have been widely reported . Several theories have been proposed, of which Folkman Klagsbrun placental theory, endothelial progenitor cell theory, hypoxia theory, and angiogenesis theory are the most accepted . GLUT‐1, Lewis Yantigen, FcyRII, merosin, and VEGF were involved in the pathophysiology of infantile hemangioma .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] The pathogenesis of hemangioma has been widely studied, and several theories have been proposed, among which endothelial progenitor cell theory, Folkman Klagsbrun placental theory, angiogenesis theory, and hypoxia theory are the most accepted. [23] To date, circRNA profiles by microarray analysis in the IHs have been reported, [11] and 234 up- and 374 downregulated circRNAs were identified in IH by microarray. [11] In this study, based on the RNA-Seq technique, we found that 249 circRNAs are dysregulated in IH including 124 upregulated and 125 downregulated circRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…On MRI, typical features in the proliferating phase include dilated feeding vessels, variable intensity T1, hyperintense T2, and flow voids around and within the mass. In the involuted phase, decrease in the vessel size is seen [20].…”
Section: Hemangiomasmentioning
confidence: 99%